Soluble Epoxide Hydrolase Inhibitor and 14,15-Epoxyeicosatrienoic Acid-Facilitated Long-Term Potentiation through cAMP and CaMKII in the Hippocampus - Han-Fang Wu; Yi-Ju Chen; Su-Zhen Wu; Chi-Wei Lee; I-Tuan Chen; Yi-Chao Lee; Chi-Chen Huang; Chung-Hsi Hsing; Chih-Wei Tang; Hui-Ching Lin (Neural Plasticity)
Epoxyeicosatrienoic acids (EETs) are derived from arachidonic acid and metabolized by soluble epoxide hydrolase (sEH). The role of EETs in synaptic function in the central nervous system is still largely unknown. We found that pharmacological inhibition of sEH to stabilize endogenous EETs and exogenous 14,15-EET significantly increased the field excitatory postsynaptic potential (fEPSP) response in the CA1 area of the hippocampus, while additionally enhancing high-frequency stimulation- (HFS-) induced long-term potentiation (LTP) and forskolin- (FSK-) induced LTP. sEH inhibitor (sEHI) N-[1-(oxopropyl)-4-piperidinyl]-N’-[4-(trifluoromethoxy) phenyl)-urea (TPPU) and exogenous 14,15-EET increased HFS-LTP, which could be blocked by an N-methyl-D-aspartate (NMDA) receptor subunit NR2B antagonist. TPPU- or 14,15-EET-facilitated FSK-mediated LTP can be potentiated by an A1 adenosine receptor antagonist and a phosphodiesterase inhibitor, but is prevented by a cAMP-dependent protein kinase (PKA) inhibitor. sEHI and 14,15-EET upregulated the activation of extracellular signal-regulated kinases (ERKs) and Ca2+/calmodulin- (CaM-) dependent protein kinase II (CaMKII). Phosphorylation of synaptic receptors NR2B and α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor subunit GluR1 was increased by TPPU and 14,15-EET administration. These results indicated that EETs increased NMDAR- and FSK-mediated synaptic potentiation via the AC-cAMP-PKA signaling cascade and upregulated the ERKs and CaMKII, resulting in increased phosphorylation of NR2B and GluR1 in the hippocampus.